REVITALISASI KESADARAN EKOLOGIS ORANG MUDA KATOLIK MELALUI KEGIATAN KONSERVASI TAMAN WISATA ALAM PONGKOR NGGULING DAN LIANG NGGAMA - Vitalis Tarsan; Yasinta S. Ental; Dionisius T. Egal; Filomena Jelita; Hermanus Saman; Hildariana S. Risda; Petronela Ratna; Carolina V. Armelia (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
One of the moral obligations in social life is to respect the nature of creation/the environment.This social moral obligation is an inseparable part of the moral obligation to God and human beings. In order to revive awareness of this obligation, the PkM team, together with Catholics Youth, carried out conservation activities at Pongkor Ngguling and Liang Nggama Nature Parks.In the implementation process, this PkM activity goes through several stages: first, the planning; second, organizing; implementation; and evaluation. The results of the activity showed that young people were very enthusiastic about participating in these activities. They are increasingly aware of their responsibility towards nature, especially their responsibility for the preservation of the Pongkor Ngguling and Liang Nggama Nature Park ecosystems. The impact of these activities for partners at the location of the activity is a change in their knowledge, attitudes/commitments, and skills in protecting and caring for nature. In the end, the partners in the location leave the habit of destroying nature and turning to the habit of protecting and preserving nature. The concrete impact is that the number and types of trees in Pongkor Ngguling and Liang Nggama are increasing, the balance of the ecosystem is maintained, coolness, beauty and security are guaranteed, and water infiltration for drinking water and rice fields is still available.